Chasing stock market returns - Nicola Borri; Alberto Cagnazzo (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2015)
The standard disclaimer in the prospectus of any mutual fund reminds investors that "past performance is not necessarily indicative of future results." Despite the disclaimer, arguably a large fraction of investors looks at recent past performance to form expectations about future returns and "times the market" balancing portfolios on the basis of these expectations. We compare return-chasing and buy-and-hold investment strategies. Return-chasing is a strategy that times investments according to past stock returns. We use quarterly net flows into equity mutual funds available to Italian investors to define the exact timing of return-chasing. The historical correlation between net flows and past stock returns is positive, so that investors invest more (less) in the stock market after high (low) past stock returns. We show that return-chasing is costly for investors: over the period 1999:Q4-2014-Q4 return-chasing, on average, under-performed a simple buy-and-hold strategy on the FTSE-MIB, the S&P 500 and the DAX 30 by as much as 5% per year. The existence of transaction costs and mutual funds' entry and exit fees imply that the effective return difference between the two strategies is even larger.
Keywords: 330